Tugas Guru Pendidikan Khusus dalam Menangani ABK di Sekolah Inklusi - Vieto Budi Utomo; Adhy Putri Rilianti (STKIP AL HIKMAH SURABAYA, 2023)
This research examines the duties of special education teachers in inclusive schools. The research method is a literature review using articles related to research titles published in the 2018-2021 period. The first search identified 24 articles, and 10 were evaluated using a thematic data approach. The results of the study show the pedagogic and non-pedagogic functions of special education teachers' tasks. Non-pedagogic tasks include emotional support, consultation and facilitation between teachers, students and parents. Pedagogic tasks include teaching, giving assignment instructions, helping students focus on completing assignments, making PPI (individual learning programs), conducting assessments, and managing student behavior. The research results also show the relevance of special education teacher education and collaborative learning between special education teachers and general education teachers. The last section discusses the limitations of the study and further research.